The current state of fishery in water bodies of the Vologda Oblast and its impact on commercial stocks of aquatic biological resources - Alexander F. Konovalov; Mikhail Ya. Borisov; Nikolay Yu. Tropin; Elena V. Ugryumova; Andrey A. Ignashev; Sergey A. Neporotovskii; Evgeniy S. Popeta; Anastasia E. Shilova; Nelya V. Dumnich (Трансформация экосистем, 2023)
The article presents a scientific review of the current state of industrial and amateur fisheries in the most important fishery water bodies of Vologda Oblast. In 2013–2022, the total annual catch of aquatic biological resources averaged 1627 tons, including 703 tons in lake Beloye, 328 – in the Rybinsk reservoir, 222 – in lake Onega, 171 – in lake Kubenskoye, 129 – in the Sheksna reservoir, and 74 tons in lake Vozhe. Bream dominated in the catches of lakes Beloye, Kubenskoye and the Sheksna reservoir (28.5–39.0%). European smelt accounted for 93.2% of the total capture in lake Onega; zope dominated in the Rybinsk Reservoir (28.4%) and pike perch – in lake Vozhe (42.5%). Lakes Beloye, Kubenskoye, Vozhe, including the Rybinsk reservoir, demonstrated maximum commercial catch (22– 35%) in December, the Sheksna reservoir – from January to March (about 48%), and lake Onega in May due to European smelt fishing (over 96%). Over the past 10 years, the stocks of the main commercial fish species in lakes Beloye and Kubenskoye, the Sheksna reservoir and lake Vozhe made up 6299, 2880 2644 and 1903 tons, respectively. Development of the total allowable catches (TAC) and the recommended volumes of production (catch) of aquatic biological resources (RC) in lake Beloye was within 59.7%; in lake Kubenskoye – 33.7%, in lake Vozhe – 31.9%, in the Sheksna reservoir – 25.8%.